HOMOCYSTEINE AS A CARDIOVASCULAR RISK FACTOR - Flavio G Jardim Filho, Marcelo (Health and Society, 2024)
This article aims to review the evidence on the relationship between homocysteine and cardiovascular disease (CVD), as well as the possible mechanisms involved and therapeutic strategies to reduce homocysteine levels. Homocysteine is an amino acid that can accumulate in the blood for various reasons, such as enzymatic defects, nutritional deficiencies, or changes in liver or kidney function. Hyperhomocysteinemia is considered an independent risk factor for CVD as it affects the vascular endothelium, promotes LDL oxidation, and stimulates thrombosis. The article presents a meta-analysis of clinical and experimental studies that investigated the association between homocysteine and CVD, the mechanisms by which homocysteine can cause vascular damage, and ways to treat hyperhomocysteinemia, mainly through supplementation with B vitamins. The article concludes that homocysteine is both a marker and a causal factor of CVD, and that reducing its levels can prevent or slow the progression of the disease.